If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42+9=n+6
We move all terms to the left:
42+9-(n+6)=0
We add all the numbers together, and all the variables
-(n+6)+51=0
We get rid of parentheses
-n-6+51=0
We add all the numbers together, and all the variables
-1n+45=0
We move all terms containing n to the left, all other terms to the right
-n=-45
n=-45/-1
n=+45
| 10x–6=19 | | 3/4x-20+7/6x+30=15/2x^2-50 | | (x+3)^2=0,16 | | 4r-32=40 | | 6x=126-8x | | (x+3)^2-0,16=0 | | 8x-10=6x-1x+4x | | 4*4.5+12=y | | 3t^2+2500t-2000000=0 | | 2x=2x+2=4x+3=4 | | 5/7x+1/3x=21 | | 7m+9=58m= | | 4y-14=18y= | | 7x+x20=180 | | (x-6)(3x-9)=0 | | 100=n+22 | | 40/x-111/x2=1 | | x-34/2=2x+1 | | -4n-3=3 | | 3.5=15=x | | 13(x-6)=4x-9 | | 5p+3=-7 | | 8x-4=8x+5÷2 | | -2w+10=-3w+60 | | -17+8e=19+4e | | 2x+5=10-5*x | | 7(7x+8)=5(6x+7)+59 | | 3x+5=4(6x-4)+63 | | 9+9=h | | 3x+12=23-2 | | (2x-1)/3=(x+3)/2 | | 3(x+4)=16x |